Barnacle inspired high-strength hydrogel for adhesive - Hao, Dezhao; Li, Xingchao; Yang, Enfeng; Tian, Ye; Jiang, Lei (Frontiers in Bioengineering and Biotechnology, 2023)
Barnacle is a widely distributed marine organism, especially known for its strong underwater adhesion ability. It is believed that a variety of adhesion mechanisms such as hydrogen bonding, electrostatic force, hydrophobic interaction is existed in the barnacle glue. However, these explanations cannot fully explain the underwater super-strong adhesion process of barnacle. In this work, inspired by barnacle glue, we designed a hydrogel system based on hydrophobic phase separation in water, which consists by the electrostatic and hydrogen bonding interactions of two charged polymers to form phase separation regions by hydrophobic interactions. This phase separation process enables the assembly of two hydrophilic polymers to form a hydrophobic and high-strength hydrogel. High strength adhesion can be achieved underwater and in a variety of organic solvents by the polymerization progress of the hydrogel. The principle in this work can deepen the understanding of the underwater adhesion principle of barnacle glue. Based on this mechanism, the hydrogel is able to prepare structural materials in water and organic solvents and rapid adhesive under water and organic solvents.